Active vitamin D supplementation and COVID-19 infections: review - Farid, Nakhoul; Rola, Nakhoul; Koch, Elias; Nakhoul, Nakhoul (Irish Journal of Medical Science, 2021)
SARS-CoV-2, causing the lethal disease COVid-19, is a public health emergency in the 2020 global pandemic. The outbreak and fast spreading of SARS-CoV-2 have a high morbidity and mortality specifically in elder patients with chronic diseases such as diabetes mellitus, arterial hypertension, chronic kidney disease, and organ transplanted patients with immunosuppressive therapy. Preliminary results support different treatments such as chloroquine and convalescent plasma infusion in severe cases, with good outcome. On the other hand, the efficacy of supplementation with active vitamin D, an immunomodulator hormone with antiinflammatory and antimicrobial effects, is unproven. A recent study reported that vitamin D attains antiviral effects, via blocking viral replication directly. SARS-CoV-2 primarily uses the immune evasion process during infection via the envelope spike glycoprotein, which is followed by a cytokine storm, causing severe acute respiratory disease syndrome and death. SARS-CoV-2, by using the well-known angiotensin-converting enzyme 2 by the protein spike, as the host receptor to enter into alveolar, myocardial, and renal epithelial cells, can be disrupted by vitamin D. However, the correlation between vitamin D levels and COVID-19 deaths in previous studies was insignificant. Retrospective studies demonstrated a correlation between vitamin D status and COVID-19 severity and mortality, while other studies did not find this correlation. Studies have shown that, vitamin D reduces the risk of acute viral respiratory tract infections and pneumonia via direct inhibition of viral replication, antiinflammatory and immunomodulatory effects. The data available today regarding the beneficial protective effect of vitamin D is unclear and with conflicting results. Large randomized control trials are necessary to test this hypothesis. In this review, we will explain the cross talk between the active vitamin D and the angiotensin-converting enzyme 2, and summarize the data from the literature.
CRIS-Team Scopus Importer:2021-01-15
Keywords: Angiotensin converting enzyme 2; COVID-19; Renin; SARS-CoV-2; Vitamin D